Genome‐wide significant localization for working and spatial memory: Identifying genes for psychosis using models of cognition. Issue 1 (14th November 2013) - Knowles, Emma E.M.; Carless, Melanie A.; de Almeida, Marcio A.A.; Curran, Joanne E.; McKay, D. Reese; Sprooten, Emma; Dyer, Thomas D.; Göring, Harald H.; Olvera, Rene; Fox, Peter; Almasy, Laura; Duggirala, Ravi; et al.
<x xml:space="preserve">Abstract</x> It is well established that risk for developing psychosis is largely mediated by the influence of genes, but identifying precisely which genes underlie that risk has been problematic. Focusing on endophenotypes, rather than illness risk, is one solution to this problem. Impaired cognition is a well‐established endophenotype of psychosis. Here we aimed to characterize the genetic architecture of cognition using phenotypically detailed models as opposed to relying on general IQ or individual neuropsychological measures. In so doing we hoped to identify genes that mediate cognitive ability, which might also contribute to psychosis risk. Hierarchical factor models of genetically clustered cognitive traits were subjected to linkage analysis followed by QTL region‐specific association analyses in a sample of 1, 269 Mexican American individuals from extended pedigrees. We identified four genome wide significant QTLs, two for working and two for spatial memory, and a number of plausible and interesting candidate genes. The creation of detailed models of cognition seemingly enhanced the power to detect genetic effects on cognition and provided a number of possible candidate genes for psychosis. © 2013 Wiley Periodicals, Inc.